PERENCANAAN ARENA GOKAR DAN RC CARS INDOOR DI PULAU KUMALA TENGGARONG PENEKANAN PADA UTILITAS - Mafazah Noviana; Cisyulia Octavia HS; Rahmat Dwi Saputra (Indonesian Society of Applied Science, 2021)
Lots of entertainment and game facilities that are no longer active on Kumala Tenggarong Island have caused a decline in the number of visitors each year, one of the facilities is outdoor Gokart Arena which currently in poor condition. The solution to increase visitor attraction and reintroduce Karting to the public is by planning Gokart Arena and RC Cars Indoor Arena as entertainment and game-themed racing facilities on Kumala Tenggarong Island. However Gokart racing activities have a negative impact on the environment such as residual liquid (oil) and solid waste (iron frame, etc.), cause noise and pollution and require good lighting for the safety of racers, therefore building design is emphasized on utilities, especially wastewater, natural lighting and natural ventilation for sustainability and comfort of buildings and the environment can be maintained properly. The application of the industrialist architectural style to the facade and interior layout through material exposure elements creates a unique character in the building with a rough and masculine look.